The Chilling Effects of Tennessee’s Prohibited Concepts Law: What Is the Potential Role of School Board Members and Superintendents? - Amanda Slaten Frasier (AERA Open)
Prohibited concept laws have a chilling effect on teaching, resulting in the erasure of social justice topics; however, the extent to which district-level actors support such laws or the role they play in perpetuating the effect is unclear. I offer a framework for understanding how district-level policy messaging contributes to the chilling effect in the context of increased partisanship and nationalized politics at the local level. I use survey data to describe school board members’ and superintendents’ perceptions of Tennessee’s PK–12 Prohibited Concepts Law. Overall, there is support for the law, but there are significant differences between the perspectives of school board members and superintendents, with the latter more likely to express neutrality. There are no differences by location, but there are significant differences based on political affiliation and perspectives about state control of curriculum, supporting the larger trend of increased nationalized partisanship of local politics.